HAJI DAN LEGISLASINYA DALAM ISLAM - Ayudin Ayudin (Prodi. Hukum Ekonomi Syariah, Fakultas Syariah, IAI Hamzanwadi Pancor Lombok Timur, 2022)
Hajj is the fifth pillar of Islam that must be carried out by every Muslim if he is able to carry it out. This obligation is once in a lifetime. The means of communication at the time of Prophet Ibrahim for those who were far away, was by camel, for long walks that reached nyanyuk from the pain of the journey was called dhamir. This leads to the conclusion that those who are ordered to come there are every human being who believes in the one and only God. More and more this appeal spread throughout the world. So that coming there no longer with camels that have been thin and squishy from a long journey, even coming from all corners of the world by planes that are faster than ships. This is also used as an argument by scholars who argue that Hajj on foot for those who are able to do it is more afdhal than Hajj by means of a vehicle. Because Allah put it first in the mention, it shows their great concern, the strength of their determination and the persistence of their intentions.